2011
DOI: 10.1073/pnas.1113521108
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide antisense transcription drives mRNA processing in bacteria

Abstract: RNA deep sequencing technologies are revealing unexpected levels of complexity in bacterial transcriptomes with the discovery of abundant noncoding RNAs, antisense RNAs, long 5′ and 3′ untranslated regions, and alternative operon structures. Here, by applying deep RNA sequencing to both the long and short RNA fractions (<50 nucleotides) obtained from the major human pathogen Staphylococcus aureus, we have detected a collection of short RNAs that is generated genome-wide through the digestion of overlapping sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
280
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(300 citation statements)
references
References 37 publications
16
280
0
4
Order By: Relevance
“…4C), suggesting that RNAIII displaces the hybrids to form more stable duplexes at these regions. Besides the changes in reactivity at the RNAIII-interacting regions, we found little reactivity change in the rest of the mgrA UTR molecule except two short regions: one near the 5′-end (nucleotides [23][24][25][26][27] and the other near the 3′-end (nucleotides 263-278). The former is near the regions that interact with RNAIII suggesting that the interaction with RNAIII induces some changes in secondary structure at nearby sequences.…”
Section: Significancementioning
confidence: 84%
See 1 more Smart Citation
“…4C), suggesting that RNAIII displaces the hybrids to form more stable duplexes at these regions. Besides the changes in reactivity at the RNAIII-interacting regions, we found little reactivity change in the rest of the mgrA UTR molecule except two short regions: one near the 5′-end (nucleotides [23][24][25][26][27] and the other near the 3′-end (nucleotides 263-278). The former is near the regions that interact with RNAIII suggesting that the interaction with RNAIII induces some changes in secondary structure at nearby sequences.…”
Section: Significancementioning
confidence: 84%
“…S1, the mgrA P2 promoter is located within the divergent NWMN_0656 coding sequence. Overlapping transcripts have been shown to be degraded by RNase III, thereby affecting mRNA level of the genes involved (27). Thus, it is possible that RNAIII could affect NWMN_0656 expression, thereby affecting mgrA mRNA levels.…”
Section: Significancementioning
confidence: 99%
“…The resulting lncRNA products might simply represent byproducts of transcription and are typically rapidly degraded after synthesis (Clark et al, 2012). (Albrecht et al, 2010(Albrecht et al, , 2011Chabelskaya et al, 2014;Chao et al, 2012;Gong et al, 2011;Grieshaber et al, 2006;Mann et al, 2012;Moon et al, 2013;Ortega et al, 2012;PadalonBrauch et al, 2008;Pfeiffer et al, 2007) crRNA, (Bhaya et al, 2011;Heidrich and Vogel, 2013;Sampson et al, 2013;van der Oost et al, 2014) (Georg and Hess, 2011;Giangrossi et al, 2010;GonzaloAsensio et al, 2013;Gottesman and Storz, 2011;Lasa et al, 2011;Lee and Groisman, 2010;Padalon-Brauch et al, 2008;Sesto et al, 2013) circRNAs rare varies arise from the 3'-5' ligation of both ends of linear RNA molecules n. a. -- (Doose et al, 2013;Vicens and Cech, 2009) - (Conway et al, 2014;Weinberg et al, 2009) Carpenter et al, 2013;Gomez et al, 2013;Iiott et al, 2014;Imamura et al, 2014;Li et al, 2014;Rapicavoli et al, 2013) poly ( …”
Section: Eukaryotic Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%
“…Ribonuclease III (RNase III) is a highly conserved endoribonuclease that specifically cleaves dsRNAs and regulates gene expression in E. coli and other bacteria (7)(8)(9)(10). Lasa et al (9) recently demonstrated that RNase III plays a central role in a type of antisense regulation specific for Gram-positive bacteria.…”
mentioning
confidence: 99%